Hubungan Riwayat Paparan Merkuri Dengan Gangguan Keseimbangan Tubuh Pada Penambang Emas Tradisional Di Desa Jendi Kecamatan Selogiri Kabupaten Wonogiri - Dewi, Novia Rina; Setiani, Onny; Suhartono, Suhartono (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2013)
Background : Gold mining in Jendi Village Selogiri Subdistrict Wonogiri District is artisanal gold mining without a permit using amalgamation process (process of extracting gold ore by mixing gold with mercury). Mercury is a neurotoxic of the central nervous system including cerebellum. The purpose of this study was to analyze the association between the history of mercury exposure and body imbalance on traditional gold miner in Jendi Village, Selogiri Subdistrict, Wonogiri District. Methods : The kind of this research is observational analytic study and the research design used was cross sectional. The population in this study are all workers in traditional gold mining region, then the sample are taken is determined based on the formula and the obtained sample size of 42 people. The research were taken through the interview, laboratory test (mercury level in the blood), and clinical examination (Romberg test). Data woukd be analyzed using Chi Square and Logistic Regression. Results : The results showed that from the four independent variables, there are two independent variables that had p values > 0,05 are the type of occupation (p value = 1,000) and duration of work per day (p value = 0,119), whereas the other two independent variables had p values ​​< 0,05 are period of work (p value = 0,004) and mercury level in the blood (p value = 0,005) so that Ho is rejected for two independent variables that had p values ​​< 0,05, which means that there is a significant correlation between period of work and mercury level in the blood with body imbalance on traditional gold miner in the Jendi Village Selogiri Subdistrict Wonogiri District. Conclusions : From this research can be concluded that as many as 88,1% of the respondents had a positive result of Romberg test and as many as 97,62% of the respondents had blood mercury level exceeding the EPA threshold value. Suggested should pay more attention to health and safety aspects of working in the gold mining process as an effort to reduce the health effects due to mercury exposure. Keywords: mercury, traditional gold miner, body imbalance